Quantitative Mapping of Phytochemical Synergy in Psidium guajava and Piper betle for Antidiarrheal Therapy: A Systematic Review and Meta-Analysis Using Radar Chart Analysis and AUC - Kintoko; Khrisna Agung Cendekiawan; Sapto Yuliani; Firdha Aprillia Wardhani (Eureka Herba Indonesia, 2026)
Infectious diarrhea constitutes a massive global health burden defined by severe gastrointestinal hypermotility, profound fluid hypersecretion, and aggressive mucosal inflammation. Conventional pharmacotherapy, including antimotility agents and broad-spectrum antibiotics, presents significant clinical limitations, including the exacerbation of antimicrobial resistance and adverse systemic effects. Phytochemical interventions utilizing Psidium guajava and Piper betle offer a robust complementary approach. However, the exact quantitative magnitude of their combined pharmacological synergy requires rigorous statistical integration. A systematic review and meta-analysis were executed utilizing PRISMA protocols. Comprehensive literature screening across major databases identified primary research manuscripts reporting precise quantitative parameters on the antidiarrheal, antimicrobial, and antioxidant properties of the targeted extracts. Extracted data variables included sample sizes, mean outcomes, and standard deviations. The Standardized Mean Difference (SMD) and 95% Confidence Intervals (CI) were calculated using a random-effects model. The multidimensional therapeutic capacity was further mapped and quantified using Radar Chart Analysis (RCA) and geometric Area Under Curve (AUC) mathematical integration. The statistical synthesis indicated that Psidium guajava profoundly suppressed gastrointestinal motility and intestinal fluid accumulation (Pooled SMD = -2.45; 95% CI: -3.10 to -1.80). Concurrently, Piper betle demonstrated immense broad-spectrum bactericidal activity and superlative free radical scavenging capacity (Pooled SMD = 3.85; 95% CI: 2.95 to 4.75). The subsequent AUC integration revealed that combining the specific phytochemical profiles of both botanical sources mathematically expanded the total therapeutic coverage by 42%. The quantitative framework confirms a highly potent synergistic mechanism. Psidium guajava selectively targets the physiological symptoms of hypermotility and secretory failure, while Piper betle aggressively eradicates the underlying pathogenic etiology and neutralizes oxidative tissue damage. This dual-action synergy provides a formidable, evidence-based foundation for the development of advanced botanical therapeutics.